An Analysis of TV Advertising and Usage of Celebrity Endorsers: A Content Analysis Approach - Prakash, Shakti; Kumar, Meenu; Prakash, Gyan (Indian Journal of Marketing, 2012)
The use of celebrities as spokespersons is one of the ways in order to position and promote the sale and popularization of products or brands. It has become a favourable marketing strategy. One of the biggest advantages of endorsing advertisements is that they ensure a high recall for the products in India. The consumers associate the symbolic attributes of the celebrities with the products and by purchasing, owning and consuming those products, consumers think of possessing those desired attributes. However, the match between endorsers and products should be perfect. In India also, celebrities are being used as product endorsers. The present study explores the extent of use of celebrities in TV commercials, their use in different product categories, the appeals of such TV commercials and the extent of use of celebrities from different fields.